River morphological behavior between two barrages on the Euphrates: A case study - Abbass, Zainab; Maatooq, Jaafar; Al-Mukhtar, Mustafa (Heritage and Sustainable Development, 2024)
The Abbassia-Shammia stream is a meandering reach in Najaf Province downstream of the Euphrates. The geomorphological traits and process-based assessment of large rivers are rarely observed globally, particularly in less developed nations. The need for such evaluation arose due to climate change, hydraulic structure construction, and the possibility of extreme droughts and floods. The hydraulic and morphological properties of the Abbassia-Shammia reach were significantly altered owing to the installation of successive barrages and climatic change. This paper aims to assess the river morphological behavior downstream of the Euphrates near the Abbassia-Shammia reach for 32 km length through the bed change investigation process, i.e. river sedimentation and erosion. The morphological performance of the Euphrates reaches between two series of barrages, namely Abbassia and Shammia, was simulated using HEC RAS2D, a tool developed by the River Analysis System program of the Hydrologic Engineering Center. The research revealed that bed change levels ranged from 5.87 meters of sedimentation to 5.720 meters of erosion. Furthermore, the results showcased how effectively the HEC RAS2D model accurately captured the features of a Euphrates section between two barrages. The results of the study provide insights into the future behavior of channels. They can help to address the issues caused by the prevailing fluvial processes such as sedimentation and erosion.